Fast and Cost-effective Calibration Method of Assembly Errors on Rotary Axes of Five-axis Machine Tools - Pan, Yongqiang; Tang, Yue (Manufacturing Technology Journal, 2025)
Five-axis machine tools are key equipment to process impellers, blades, and other precision mechanical parts. However, the accuracy of the machine tools is significantly influenced by assembly errors, and over time, these errors may change, further impacting the machining accuracy. Traditional laser interferometry technology can identify such assembly errors. The development of on-machine measurement technology has enabled methods that utilize on-machine measurement for assembly error calibration, improving calibration efficiency. The study introduces an efficient method to calibrate the assembly errors of machine tool rotary axes. First, the kinematic model for a machine tool is develop. Subsequently, utilizing on-machine measurement technology, the assembly errors of the rotary axes are calibrated, and the calibration uncertainty is analyzed. The results of the experiment confirm the validity of the calibration method. This method can be applied for periodic calibration of machine tool assembly errors, continuous monitoring variations in machine tool accuracy and ensuring the stability of machining quality.
Keywords: Assembly errors; Calibration; Machine tools; On-machine measurement